Apuntes sobre poesía y ley en Ennio Moltedo y José Watanabe (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
This paper explores the relationship between poetry and law in two different poetry collections: Ennio Moltedo's La Noche (1999) and Jose Watanabe's Antígona (2000). The transformation of space or territory in the context of the authoritarian persistence of neoliberal Chile and the enslavement of bodies in the context of Fujimori's political brutality in Peru are two examples of how these relations allow writing to confront other realities. The weight of the law will be persistently represented in both spatiality and corporeality, giving rise to poetry as a language that would allow the subjects to heal from the failures that these procedures have created.
Keywords: Poetry; Law; Ennio Moltedo; José Watanabe